El Debate Necesario. Candidatos a la Alcaldía de Bucaramanga - Muñoz Villareal, Sergio Isnardo; Toledo, Carlos Francisco; Beltrán, Jaime Andrés; Cárdenas Rey, Juan Carlos; García Gómez, Ariel Gerardo (Universidad Autónoma de Bucaramanga UNAB, 2021)
03:10:47 horas